On Regular Generalized Sampling in T-Invariant Subspaces of a Hilbert Space: An Overview. (25th April 2020) - García, Antonio G.; Muñoz-Bouzo, María J.; Pérez-Villalón, Gerardo
Abstract: A regular generalized sampling theory in some structured T -invariant subspaces of a Hilbert space H, where T denotes a bounded invertible operator in H, is established in this paper. This is done by walking through the most important cases which generalize the usual unitary sampling settings.